Light : A Very Short Introduction - Walmsley, Ian A. (United Kingdom Oxford University Press, 2015)
"Introduces readers to the basic properties of light--reflection and refraction, polarization, and interference--before moving on to how light is generated, its role in relativity, and quantum effects it exhibits."--Inside front cover.
Include Index
Keywords: Light -- Walmsley, Ian A